Testing asteroseismic scaling relations using eclipsing binaries in star clusters and the field - Brogaard, Karsten; Thygesen, Anders (Arxiv, 2016)
The accuracy of stellar masses and radii determined from asteroseismology is not known! We examine this issue for giant stars by comparing classical measurements of detached eclipsing binary systems (dEBs) with asteroseismic measurements from the Kepler mission. For star clusters, we extrapolate measurements of dEBs in the turn-off region to the red giant branch and the red clump where we investigate the giants as an ensemble. For the field stars, we measure dEBs with an oscillating giant component. These measurements allow a comparison of masses and radii calculated from a classical eclipsing binary analysis to those calculated from asteroseismic scaling relations and/or other asteroseismic methods. Our first results indicate small but significant systematic differences between the classical and asteroseismic measurements. In this contribution we show our latest results and summarize the current status and future plans. We also stress the importance of realizing that for giant stars mass cannot always be translated to age, since an unknown fraction of these evolved through a blue straggler phase with mass transfer in a binary system. Rough estimates of how many such stars to expect are given based on our findings in the open clusters NGC6819 and NGC6791.